(untitled) (Research, Society and Development, 2021)
Introduction: The elderly represents 14.6% of the population of the state of Tocantins, reaching a number of 228,000 people. The occurrence of fractures in this population is related to greater bone fragility resulting from degenerative physiological contexts that increase the risk of falls, several associated factors and predisposing factors, the most frequent being various neurological disorders, the use of drugs that act on the psyche and that can affect balance, greater muscle deficit and the presence of arthropathies and various deficiencies resulting from different diseases that may be present. Methodology: This is an analytical descriptive research, with a quantitative approach, in which data was searched in the DATASUS Information System over a decade from 2010 to 2020. Results: A number of 7,382 fractures were found in a decade in the state of Tocantins, which showed a greater number of fractures in the elderly aged 60 to 69 years, with a prevalence in women and fractures of other limbs. Conclusion: The highest number of fractures was found in the younger elderly group (60 to 69 years), thus presenting a higher risk of trauma. The highest incidence of fractures in relation to gender was female, and the largest number of fractures found in a decade were fractures of other limb bones.